Cambodia : 2008 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
This staff report for Cambodia's 2008 Article IV Consultation describes economic developments and policies. Growth is slowing, liquidity is tightening, and, as a result, banks' balance sheets are coming under strain. Competitiveness has eroded given the recent sharp real appreciation of the Cambodian riel and U.S. dollar. The immediate risks to Cambodia arise from liquidity shortages among banks owing to a sharp slowing in external inflows and deposit growth. Bank lending has moderated, construction activity has slowed, and property prices, after reaching historic peaks, appear to be declining.